PEMANFAATAN EKSTRAK ETANOL KAYU MANIS (CINAMOMMUM BURMANII) SEBAGAI REPELLENT ALAMI NYAMUK AEDES AEGYPTI - Rosa Devitria (Jurnal Sains dan Teknologi Laboratorium Medik, 2021)
Dengue fever is a disease transmitted by female Aedes aegypti mosquitoes that have been infected with the dengue virus from other dengue fever sufferers. This disease is one of the infectious diseases that often causes outbreaks and causes death and can cause Extraordinary Events (KLB). One way to prevent the spread of dengue fever is by controlling the Aedes aegypti mosquito, this control can be done by using a repellent. The purpose of this study was to determine the effect of cinnamon ethanol extract (Cinnamomum burmanii) as a natural insecticide repellent against Aedes aegypti mosquitoes and to determine the active compounds contained in the rhizome of jeringau. This research was conducted using an experimental laboratory method with a focus research design to determine the effectiveness of the ethanolic extract of cinnamon (Cinnamomum burmanii) as a repellent against the Aedes aegypti mosquito. Based on the research, it was obtained at a concentration of 5% of mosquitoes that stayed away as many as 8 (80%) for 5 minutes, a concentration of 10% of mosquitoes that stayed away as many as 90 (90%) for 5 minutes, and at a concentration of 20% of mosquitoes that stayed away as many as 10 ( 100%) for 5 minutes. While the control (+) within 5 minutes of mosquitoes away as much as 10 tails (100%) and control (-) there are no mosquitoes that move away as much as 10 tails (0%). The results of this study can be concluded that the ethanol extract of cinnamon (Cinnamomum burmanii) is the most effective as a repellent at a concentration of 20%. This extract is able to act as a repellent and function as a natural insecticide against Aedes aegypti mosquitoes.